Respuesta :
Since we are given with the final price already, we calculated for the initial price backwards.
(1) 227.83 = (1 - 0.31)x₁
x₁ = 330.19
(2) 330.19 = (1 + 0.13)x₂
x₂ = 292.20
(3) 292.29 = (1 - 0.24)x₃
x₃ = 384.48
(4) 384.48 = (1 + 0.35)x₄
x₄ = 284.80
(5) 284.80 = (1 - 0.20)x₅
x₅ = 355.99 or 356
Therefore, the original price of the mattress is ~ $356.
(1) 227.83 = (1 - 0.31)x₁
x₁ = 330.19
(2) 330.19 = (1 + 0.13)x₂
x₂ = 292.20
(3) 292.29 = (1 - 0.24)x₃
x₃ = 384.48
(4) 384.48 = (1 + 0.35)x₄
x₄ = 284.80
(5) 284.80 = (1 - 0.20)x₅
x₅ = 355.99 or 356
Therefore, the original price of the mattress is ~ $356.
Answer: The answer is A or 356
Step-by-step explanation: I got 100% on test